CROSS SECTION RETURN SAHAM DAN KEBIJAKAN MONETER - Asma, Rusdayanti (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2006)
Abstract This research aimed to analyze the influence of beta, size and price-to-book value to stock return and also to determine whether influence given by those three factors will differ at different monetary condition. Test conducted to 152 stocks which are traded actively in BEJ at period of July 2000 to June 2003. Early test result indicated that independent variables namely beta, size and PBV have a significant influence to stock return. Test reenacted by separating sample between periods which is expansive and restrictive, the result indicated that on expansive period beta did not have significant result, while on restrictive period all of variables have significant result. After conducting the interaction test by including the monetary policy as dummy variable, the test resulted that monetary policy did not affect the relation between PBV and stock return, while beta and size indicated the significant result, it means that the relation of those two variables to stock return is indeed influenced by monetary policy. Keywords: beta, size, price-to-book value, stock return, monetary policy